2015
DOI: 10.1109/tdei.2015.7076783
|View full text |Cite
|
Sign up to set email alerts
|

Thermal aging effects on the moisture equilibrium curves of mineral and mixed oil-paper insulation systems

Abstract: Moisture equilibrium curves are well accepted methods for moisture estimation of insulation paper in field transformers. The thermal aging effects on moisture partition diagrams of mineral oil-paper and a new aging-resistant mixed oil-paper insulation system were studied. The purpose was to assess the moisture content accurately, particularly in transformers used for long-term operations. Thermal aging experiment was conducted at 130 °C for 80 days, and moisture equilibrium curves at five different aging degre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…The hygroscopicity of the dried new pressboard and the pressboard coated for PTFE was also compared at here. According to the moisture equilibrium experiment that was done by our team [ 28 ], the dried pressboard samples were placed into a humidity chamber. The temperature of the humidity chamber was set to 60 °C and the relative humidity was set to 60%.…”
Section: Resultsmentioning
confidence: 99%
“…The hygroscopicity of the dried new pressboard and the pressboard coated for PTFE was also compared at here. According to the moisture equilibrium experiment that was done by our team [ 28 ], the dried pressboard samples were placed into a humidity chamber. The temperature of the humidity chamber was set to 60 °C and the relative humidity was set to 60%.…”
Section: Resultsmentioning
confidence: 99%
“…They found that the rate of space charge formation can be increased when the moisture content is lower than 7%, but is suppressed when moisture content is higher than 9% [10]. The results of experiments on accelerated thermal ageing have shown that the moisture absorption capacity of insulation paper decreases with deepening ageing degree whereas that of oil increases [11]. The ratio of moisture content in paper to that in oil decreases with decreasing polymerisation according to similar research [12].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been realized that thermal aging affects the moisture absorption capacity of insulation paper obviously [22]- [24], i.e., the hydrophilicity of insulation paper is worse with aging. The effects of thermal aging on the moisture diffusion and the equilibrium moisture content of oil-immersed insulation paper have been reported in [5], [14], [23]. However, the characteristics of moisture diffusion in non-oil-immersed insulation paper are different from that of oil-immersed insulation paper [22].…”
Section: Introductionmentioning
confidence: 99%